Asksia AI LOGO

Sia

younglife's Question
Math
Posted 9 months ago
Calculate the derivative of the function g(x)=e2xg(x) = e^{2x}.
Sign in to unlock the answer
Answer from Sia
Posted 9 months ago
Solution by Steps
step 1
To find the derivative of the function g(x)=e2xg(x) = e^{2x}, we use the chain rule
step 2
The chain rule states that if y=f(u)y = f(u) and u=g(x)u = g(x), then dydx=dydududx\frac{dy}{dx} = \frac{dy}{du} \cdot \frac{du}{dx}
step 3
Here, f(u)=euf(u) = e^u and u=2xu = 2x. So, dydu=eu\frac{dy}{du} = e^u and dudx=2\frac{du}{dx} = 2
step 4
Applying the chain rule: ddx(e2x)=e2x2=2e2x\frac{d}{dx}(e^{2x}) = e^{2x} \cdot 2 = 2e^{2x}
Answer
The derivative of g(x)=e2xg(x) = e^{2x} is 2e2x2e^{2x}.
Key Concept
Chain Rule
Explanation
The chain rule is used to differentiate composite functions. In this case, e2xe^{2x} is a composite function where the outer function is eue^u and the inner function is 2x2x.

Not the question you are looking for? Ask here!

Enter question by text

Enter question by image

Unlock Smarter Learning with AskSia Super!

Join Super, our all-in-one AI solution that can greatly improve your learning efficiency.

30% higher accuracy than GPT-4o
Entire learning journey support
The most student-friendly features
Study Other Question